Enhancing Monkeypox diagnosis: a machine learning approach for skin lession classification - Nazmee, Namirah; Mahmud, Sadia; Ali, Mashyat Samiha; Alam, Khusbo (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.